Can digital transformation affect the exports of foreign trade firms? - Chen, Fuyong; Xin, Yingying; Ma , Nana (Transformations In Business & Economics, 2025)
In the context of intensified global competition, it is crucial to effectively promote firm exports and improve firm export levels. However, many factors affect firm exports, including the macro level, the micro level, the institutional level, the firm financial level, etc. Digital transformation reflects the innovation and drastic changes at the technological level of firms. At present, the impact of digital transformation within firms on exports is not clear. Will it affect the export level of firms? To fill this research gap, based on the export competition theory and human capital theory, using the data of China’s foreign trade listed companies from 2010 to 2022 and the OLS multiple regression analysis model, the impact of digital transformation on the export competitiveness of firms was explored. Additionally, the differences in the nature of property rights and the moderating role of human capital in the above relationship were discussed. Results show that digital transformation can significantly promote the improvement of the export level of foreign trade firms. Compared with state-owned firms, digital transformation in non-state-owned firms has a more significant effect on improving the export level of foreign trade firms. Executive human capital is an important factor affecting the efficiency of firm decision-making. Higher human capital can strengthen the role of digital transformation in improving the export level of foreign trade firms. The conclusions enrich the studies on the economic consequences of firm digital transformation and also provide empirical evidence on how to promote the export of foreign trade firms and improve the export competitiveness of foreign trade firms.